PARPOL PETANI DALAM PERSPEKTIF KETAHANAN PANGAN - Sutawi, Sutawi (Jurnal Bestari, 2008)
Food scurity plays an important role in national development since it creates Indonesian prosperity, there are three parties that should become prosperous through food; those are farmers, distributors and consumers. Food security, defined as food availability, regarding the adequacy and low price, couse farmers prosperity get worst and make Indonesia the biggest net-imperter of food. Many countries have proven that the agricultural developments, including farmers prosperity, are not only determined by technical and economical factors, but also influenced mostly by political factor. political party built by farmers community is the most important way to develop agriculture sector, to buid food security and to improve farmer community's prosperity